The Reliability and Validity of Gluteal Endurance Measures (GEMs) - B J Lehecka; Barbara S Smith; Todd Rundell; Thomas A Cappaert; Nils A Hakansson (North American Sports Medicine Institute, 2021)
# Background The gluteals have unique morphology related to muscle endurance, including moderate fiber sizes and a majority of Type I endurance fibers. Evidence suggests gluteal endurance is related to low back pain, running kinematics, balance, posture, and more. However, reliable and valid measures specific to gluteal endurance are lacking in the literature. # Hypothesis/Purpose The purpose of this study was to examine the intra- and inter-rater reliability of two gluteal endurance measures (GEMs) for clinical use. It also aimed to examine validity for the two measures by using electromyography (EMG), recording reasons for task failure, and analyzing differences between demographic groups. # Study Design Cross-Sectional # Methods Sixty-eight males and females with and without recurrent low back pain aged 18-35 years were recruited from a university population. Electromyography electrodes were placed on subjects' gluteus maximus and gluteus medius, and each subject performed three trials of GEM-A (abduction endurance) and GEM-B (bridging endurance). Hold times, EMG median frequency (MF) data, and subjective reasons for task failure were analyzed. # Results Both GEMs demonstrated high intra-rater reliability (ICC = 0.87-0.94) and inter-rater reliability (ICC = 0.99). Mean hold times were 104.83 ± 34.11 seconds for GEM-A (abduction endurance) and 81.03 ± 24.79 seconds for GEM-B (bridging endurance). No statistically significant difference was found between subjects with and without recurrent LBP. Median frequency data validated the onset of gluteal fatigue during both measures. Posterolateral hip (gluteal) fatigue was reported as the primary reason for task failure in 93% and 86% of subjects for GEM-A and GEM-B, respectively. # Conclusion This seminal study of GEM-A (abduction endurance) and GEM-B (bridging endurance) found both measures to be reliable and valid measures of gluteal endurance. Further examination of the GEMs in samples with different types of LBP or hip pain is recommended. # Level of Evidence 3